Assessment of hygienic practices among pig slaughterhouses and markets in Chiang Mai Province, Thailand - Jenpanich, C.; Unger, Fred; Alter, T.; Chaisowwong, W. (Freie Universität Berlin, 2015)
Insufficient hygienic practices of food handlers such as poor personal hygiene associated with foodborne illness can lead to crosscontamination along food chains. This study aimed to assess knowledge, attitudes and practices (KAP) of food handlers regarding food safety and hygienic practices in addition to assess the level of microbiological hygiene indicators. A cross-sectional study was conducted in 16 slaughterhouses and 31 markets in Chiang Mai province. Overall 32 slaughterhouse workers and 51 pork sellers were assessed to determine their KAP by questionnaires including likert-scales. Microbiological hygiene indicators were determined by conventional cultural methods. KAP results indicated a high level of knowledge (80 to 100%) concerning cross contamination, personal hygiene and time-temperature control but hold medium level (50 to 75%) for foodborne illness. Eighty-five percent of food handlers knew that good personal hygiene could prevent foodborne disease. Identified gaps between attitudes and practices indicated that some hygiene measures are inappropriate in the context of their practical implementation and some of these hygiene practices are not in accordance with their socioeconomic status. There were variations of knowledge between slaughterhouse workers and sellers. Mean of aerobic bacteria count from carcass swabs at slaughterhouses and pork samples at markets were 3.09±1.34 log10 cfu/cm2 and 5.50±0.39 log10 cfu/g. respectively. The mean Enterobacteriaceae count was 0.03±1.08 log10 cfu/cm2 and 2.55±1.43 log10 cfu/g respectively. Existing hygiene recommendations should be revised and adjusted according to their practical implementation considering also socio-economics and other factors of food handlers. Our results provide basic information for educational programs in order to improve knowledge of food safety and hygiene practices and narrow down the gaps between attitudes and practices.